Therapeutic Efficacy of Bromelain in Alveolar Ridge Preservation - Glauco Chisci; Luca Fredianelli (MDPI AG, 2022)
Most of research in regenerative oral surgery describes materials or techniques for increasing volumetric results for implant-supported prosthesis. The use of bio-materials in alveolar ridge preservation after tooth extraction commonly leads to a delayed recovery. Bromelain is an enzyme that belongs to a family of proteolytic enzymes derived from the stem of the pineapple plant (Ananas comosus) with effectiveness in decreasing the inflammation development and swelling. The present paper reports a prospective comparative study performed in order to test the possible use of oral bromelain 40 mg in alveolar ridge preservation. Evaluations were performed at three time points after the surgery: after 2 days (t1), after 7 days (t2) and after 14 days (t3). A statistically significant difference among patients that used bromelain and patients that used placebo resulted among the use of bromelain and lower Visual Analogue Scale (VAS) at t1 (r = −0.75, p = 0.0067), t2 (r = −0.90, p = 0.0001) and t3 (r = −0.8566, p = 0.0008). Bromelain therapy reported a statistically significant difference among patients that used bromelain and patients that used placebo even with regards to the use of bromelain and postoperative swelling at t1 (r = −0.79, p = 0.0034), t2 (r = −0.81, p = 0.0020) but not at t3 (r = −0.34, p = 0.2967). With the result of the present paper, and the poorness of contraindication of the investigated drug, bromelain may be suggested to be used for patients that undergo to alveolar ridge preservation after tooth extraction.